Catalytic peptide-based coacervates for enhanced function through structural organization and substrate specificity - Reis, David Q.P. (2024)
This work was partially supported by PPBI - Portuguese Platform of BioImaging (PPBI-POCI-01-0145-FEDER-022122) co-funded by national funds from OE - \u201COr\u00E7amento de Estado\u201D and by european funds from FEDER - \u201CFundo Europeu de Desenvolvimento Regional. La Caixa Junior Leader Fellowship (LCF/BQ/PI20/11760012) financed by\u201Dla Caixa\u201D Foundation (ID 100010434) and a Maratona da Sa\u00FAde award. The NMR spectrometers at CERMAX, ITQB-NOVA, Oeiras are funded by FCT through project AAC 01/SAICT/2016, while those from FCT-NOVA are part of the National NMR Network and are supported by FCT (ROTEIRO/0031/2013) cofounded by FEDER through COMPETE 2020, POCI, PORL and FCT through PIDDAC. Publisher Copyright: © The Author(s) 2024.